2006
DOI: 10.1177/154405910608500112
|View full text |Cite
|
Sign up to set email alerts
|

Overall Activity of All Masticatory Muscles during Lateral Excursion

Abstract: Quantification of the overall activity of every masticatory muscle is requisite for the analysis of stomatognathic function, which has not been accomplished by conventional electromyography. We used positron emission tomography and 18F-fluoro-deoxy-glucose to quantify the overall activity of every masticatory muscle during lateral excursion, and to evaluate the relative contribution of each masticatory muscle to lateral excursion. The present study suggested that lateral and medial pterygoid muscles are more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The mean ΔT2 value of the ipsilateral medial pterygoid muscle was higher (although not significantly) than that of the contralateral medial pterygoid muscle during unilateral gum chewing. In contrast, a previous FDG‐PET study showed that the activity of the contralateral medial pterygoid muscle, which is associated with a forward force to pull on the contralateral angle of the mandible, was higher than that of the ipsilateral medial pterygoid muscle during lateral excursion (Yamaguchi et al , 2006). Another study showed that the medial pterygoid muscle was associated with the vertical and anterior bite forces, and that the activity of the contralateral medial pterygoid muscle early in the closing phase was associated with marked forward and lateral movement of the jaw toward the chewing side during unilateral chewing (Wood, 1986).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The mean ΔT2 value of the ipsilateral medial pterygoid muscle was higher (although not significantly) than that of the contralateral medial pterygoid muscle during unilateral gum chewing. In contrast, a previous FDG‐PET study showed that the activity of the contralateral medial pterygoid muscle, which is associated with a forward force to pull on the contralateral angle of the mandible, was higher than that of the ipsilateral medial pterygoid muscle during lateral excursion (Yamaguchi et al , 2006). Another study showed that the medial pterygoid muscle was associated with the vertical and anterior bite forces, and that the activity of the contralateral medial pterygoid muscle early in the closing phase was associated with marked forward and lateral movement of the jaw toward the chewing side during unilateral chewing (Wood, 1986).…”
Section: Discussionmentioning
confidence: 68%
“…FDG‐PET has been used to evaluate muscle activity by measuring intramuscular variation in glucose metabolism within exercising skeletal muscles (Fujimoto et al , 1996; Pappas et al , 2001). This approach allows simultaneous quantification of the overall activity of individual masticatory muscles during chewing and lateral excursion (Rikimaru et al , 2001; Yamaguchi et al , 2006). However, FDG‐PET scanning cannot be performed repetitively in an individual subject because of exposure to the 18 F radioisotope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,20,37,38 Experimentally gained data with regard to the EMG patterns of masseter and sternocleidomastoid muscles during the jaw posture tasks studied promote a better understanding of the control strategies of the motor system. 39 The results of the present study illustrate that there is a close association between jaw posture tasks and the action of the masseter and sternocleidomastoid muscles.…”
Section: Resultsmentioning
confidence: 99%
“…Both the LP and the PM are involved in the horizontal movement of the mandible; the LP moves the mandible on the opposite side of its contraction while the PM pulls the mandible forward [20]. The PM belongs to the group of the elevator muscles of the mandible, while the LP is part of the group of muscles that depress the mandible [21].…”
Section: Introductionmentioning
confidence: 99%